The Causal Relationship Between Internal Motivation and Learning Readiness With the Cognitive Learning Achievement in Learning Biology at SMA Negeri 1 Cawas in Class Year of 2011/2012. - Novita Tyas Suviana; Puguh Karyanto; Bowo Sugiharto (BIO-PEDAGOGI, 2012)
This research is aimed to know causal relationship between:           1) internal motivation and cognitive learning achievement in learning Biology,        2) internal motivation and learning readiness in leaening Biology, 3) learning readiness and cognitive learning achievement in learning Biology, 4) internal motivation and cognitive learning achievement through learning readiness in learning Biology.This was a correlational research and conducted upon high school student at SMA Negeri 1 Cawas in academic year in 2011/2012. The sample was taken among 100 samples of student using stratified random sampling technique.      Documentation technique was used to uncover student’s cognitive learning achievement, while internal motivation and learning readiness was measured by using queationnaire. The obtained data was analysed using path analysis in SPSS 16.The result showed that (1) there is causal corellation between internal motivation and cognitive learning achievement in learning Biology, 2) there is causal   corellation between internal motivation and learning readiness in learning Biology, 3) there is causal corellation between learning readiness and cognitive learning achievement in learning Biology, 4) there is causal corellation between internal motivation and cognitive learning achievement through learning readiness in learning Biology. The aforementioned corellation are considured as significant and positive valuable. This research showed that learning readiness can be a       intervening variable for the corellation between of  internal motivation and cognitive learning achievement. Key Words: internal motivation, learning readiness, cognitive learning achievement of biology, path analysis